2002
DOI: 10.1086/338115
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliHarboring Shiga Toxin 2 Gene Variants: Frequency and Association with Clinical Symptoms

Abstract: Shiga toxin (Stx)-producing Escherichia coli (STEC) from patients with hemolytic-uremic syndrome (HUS), patients with diarrhea without HUS, or asymptomatic subjects were genotyped to assess associations between stx2 variants and clinical manifestations of infection. Neither stx2d nor stx2e was found in 268 STEC isolates from patients with HUS. Of 262 STEC isolates from patients with diarrhea, stx(2d) was found in 41 (15.6%; P<.000001), and stx2e was found in 12 (4.6%; P=.0004). The stx2c genotype frequency was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

34
651
7
20

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 676 publications
(712 citation statements)
references
References 48 publications
34
651
7
20
Order By: Relevance
“…The low incidence of Stx2e strains in human patients could indicate that most of these strains cannot colonize or may infect but do not cause disease in humans. This is supported by epidemiological findings indicating that Stx2e strains are very rarely isolated from humans, and those patients show mild diarrheal symptoms or are asymptomatic carriers (4,17,39,42). In a previous study we have found that Stx2e-producing strains differ largely in the amount of Stx2e produced (2).…”
supporting
confidence: 62%
See 3 more Smart Citations
“…The low incidence of Stx2e strains in human patients could indicate that most of these strains cannot colonize or may infect but do not cause disease in humans. This is supported by epidemiological findings indicating that Stx2e strains are very rarely isolated from humans, and those patients show mild diarrheal symptoms or are asymptomatic carriers (4,17,39,42). In a previous study we have found that Stx2e-producing strains differ largely in the amount of Stx2e produced (2).…”
supporting
confidence: 62%
“…The stx 2e gene is associated with E. coli serotypes that have not been described as bacterial hosts for other types of Stx so far (4,16,17,39,42). Additionally, the stx 2e gene was not reported to be present in typical and atypical EHEC strains causing bloody diarrhea and HUS, except for one case reported in 1994 (11,36,43).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Stx are formed by a single A subunit, which possesses N-glycosidase activity to the 28S rRNA and promotes protein synthesis inhibition in eukaryotic cells, and five B subunits, which bind to globotriaosylceramide (Gb3Cer) at the surface of host cells (9,10). Although two major types (Stx1 and Stx2) and several subtypes (variants) have been described, Stx2 and its variant Stx2c are the toxins found most frequently in severe HUS cases among EHEC-infected subjects (11,12). Stx1 and Stx2 differ significantly both in amino acid sequences and in biological functions (13,14).…”
mentioning
confidence: 99%